2015
DOI: 10.2147/dddt.s86616
|View full text |Cite
|
Sign up to set email alerts
|

Development of telmisartan in the therapy of spinal cord injury: pre-clinical study in rats

Abstract: BackgroundDecrease of peroxisome proliferator-activated receptors-δ (PPARδ) expression has been observed after spinal cord injury (SCI). Increase of PPARδ may improve the damage in SCI. Telmisartan, the antihypertensive agent, has been mentioned to increase the expression of PPARδ. Thus, we are going to screen the effectiveness of telmisartan in SCI for the development of it in clinical application.MethodsIn the present study, we used compressive SCI in rats. Telmisartan was then used to evaluate the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Telmisartan showed to increase level of ~40 kDa PPAR-β/δ expression after spinal cord injury, which was associated with beneficial effects manifested by improved motor function and pain responses. 45 Consistent with this finding, increased level of nuclear ~40 kDa PPAR-β/δ in our study was accompanied by improved performance in rotarod test assessing motor function. This protective mechanism in SCI may be mediated through phosphorylation of 5' AMP-activated protein kinase (AMPK).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Telmisartan showed to increase level of ~40 kDa PPAR-β/δ expression after spinal cord injury, which was associated with beneficial effects manifested by improved motor function and pain responses. 45 Consistent with this finding, increased level of nuclear ~40 kDa PPAR-β/δ in our study was accompanied by improved performance in rotarod test assessing motor function. This protective mechanism in SCI may be mediated through phosphorylation of 5' AMP-activated protein kinase (AMPK).…”
Section: Discussionsupporting
confidence: 91%
“…This protective mechanism in SCI may be mediated through phosphorylation of 5' AMP-activated protein kinase (AMPK). 45 The action of telmisartan was inhibited by a blockade of the receptor with GSK0660, which resulted in decrease of PPAR-β/δ expression level. Those results suggest, that the restoration of ~40 kDa PPAR-β/δ expression was responsible for therapeutic potential of telmisartan in rats with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TEL-induced stimulation of I Na was not accounted for by either binding to AT1 receptors or activation of PPAR-γ (Mogi et al, 2008). In this scenario, it is therefore possible that TEL confers protection against ischemic or traumatic brain damage possibly as a result of its activation of Na V channels, independent of its agonistic effects on PPAR-γ activity (Mogi et al, 2008;Wang et al, 2014;Kono et al, 2015;Lin et al, 2015;Villapol et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that TEL ameliorates impaired cognitive functions (Mogi et al, 2008;Du et al, 2014;Haruyama et al, 2014) and is beneficial for traumatic or ischemic brain injuries (Łukawski et al, 2014;Wang et al, 2014;Kono et al, 2015;Lin et al, 2015;Villapol et al, 2015) although the underlying mechanism has not been fully elucidated. To what extent this compound perturbs ion-channel activity and neuronal excitability in hippocampal neurons remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The analgesic and anti-inflammatory effects of telmisartan have been evaluated in preclinical studies of different types of neuropathic pain [65][66][67][68]. The main mechanism underlying these effects is partial activation of PPAR-γ receptors [65,66,68], but according to one study, telmisartan reduced thermal and mechanical hypersensitivity by inhibiting CYP2J2 [67].…”
Section: Discussionmentioning
confidence: 99%